Autogobierno y modernización de Galicia durante las cuatro últimas décadas - Xoaquín Fernández Leiceaga; Santiago Lago Peñas (Cahiers de Civilisation Espagnole Contemporaine)
The four decades of self-government in Galicia (1980-2020) have been a success. The size of its economy has doubled, and per capita income has grown remarkably, thanks to profound structural change, with persistent reduction of the agricultural weight accompanied by high productivity gains. In this period, Spain became democratized, decentralized, entered the European Union and built a comparable welfare state. In summary, the changes have favored the progress of Galicia and a more positive insertion in the Spanish economy. European funds have facilitated development and companies have been able to adapt to a more internationalized environment. The infrastructures have improved. Difficulties persist: regressive demographics, the abandonment of fertile agricultural land or the difficulty in attracting foreign investment. And challenges derived from digitization, the energy transition or globalization. But self-government will allow us to channel our energies better.